2015
DOI: 10.1038/cdd.2014.238
|View full text |Cite
|
Sign up to set email alerts
|

CXXC5 is a negative-feedback regulator of the Wnt/β-catenin pathway involved in osteoblast differentiation

Abstract: The positive roles of the Wnt/β-catenin pathway in osteoblast differentiation and bone mineral density (BMD) maintenance have been clearly demonstrated in both animal experiments and clinical investigations. CXXC finger protein 5 (CXXC5), a recently identified negative regulator of the Wnt/β-catenin pathway, showed altered cellular localization and function, which were dependent on the cell type in previous studies. However, the in vivo function of CXXC5 has not been clearly investigated yet. Here, we characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 24 publications
(30 reference statements)
2
83
0
Order By: Relevance
“…These findings are relevant to studies involving late osteoblast functions ( 36 , 37 ). Additional investigations will aim to fully reproduce the bone cell microenvironment by combining our 3D culture system with osteoclast precursors also derived from mPSCs.…”
Section: Discussionmentioning
confidence: 67%
“…These findings are relevant to studies involving late osteoblast functions ( 36 , 37 ). Additional investigations will aim to fully reproduce the bone cell microenvironment by combining our 3D culture system with osteoclast precursors also derived from mPSCs.…”
Section: Discussionmentioning
confidence: 67%
“…Apart from being a transcription factor, CXXC5 was shown to act as a negative-feedback regulator of Wnt/β-catenin signaling by interacting with the cytoplasmic scaffold Dishevelled (Dvl) proteins in osteoblast differentiation and bone formation33, cutaneous wound healing and collagen production34, neural stem cell differentiation and telencephalon development13. CXXC5 was also reported to interact with and require for DNA damage-induced ATM phosphorylation, subsequent activation of p53, cell cycle arrest and apoptosis35.…”
Section: Discussionmentioning
confidence: 99%
“…In pre‐osteoblasts, Tcf/β‐catenin complex binds with Runx2 in their nucleus and regulates osteogenic genes specifically (Reinhold & Naski, ). Among the direct transcriptional target genes of Wnt/β‐catenin signaling, an osteogenic gene, Fgf18 (Reinhold & Naski, ), but not oncogenic genes ( c‐Myc and cyclin D1 ) (He et al , ; Shtutman et al , ), were induced by Wnt3a treatment in pre‐osteoblasts (Kim et al , ). We also did not observe any sign for cancer development in CXXC5 −/− mice, grown up to 1.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we suggested the Dvl–CXXC5 interaction as a negative feedback mechanism of the Wnt/β‐catenin pathway and as a potent target for bone anabolic agents (Kim et al , ). We confirmed this hypothesis using a newly synthesized competitor peptide of the Dvl–CXXC5 interaction, which induced osteoblast differentiation and enhanced bone formation of ex vivo ‐cultured calvariae (Kim et al , ). Here, we identified KY‐02061, a small‐molecule inhibitor of Dvl–CXXC5 interaction by establishing a new Dvl–CXXC5 in vitro binding assay system and verified the competitor peptide‐mimicking effects of this compound.…”
Section: Introductionmentioning
confidence: 99%